Reshaping living space in malaysia from the evolving work pattern - Ma'rof, Aini Azeqa; Pang, Jian Sheng; Mohd Noor, Mohd Zairul (Human Resource Management Academic Research Society, 2024)
The shift in work patterns in Malaysia, accelerated by technological advancements and the COVID-19 pandemic, necessitates a reevaluation of living environments. Traditional office- based work is giving way to remote and hybrid models, requiring homes to become multifunctional spaces. However, existing housing designs often fail to meet the demands of remote work, leading to decreased productivity and well-being. This study addresses these challenges by employing a mixed-methods approach to examine the relationship between evolving work patterns and living environments in Malaysia. The research design includes both quantitative surveys and qualitative interviews. A structured survey will be distributed to a diverse sample of remote workers across different industries to assess their living and working conditions, productivity levels, and well-being. Qualitative interviews will be conducted with selected participants to gain deeper insights into their experiences and challenges in adapting their living spaces for remote work. Data analysis will involve statistical methods to identify correlations and themes from qualitative data will be coded and analyzed using thematic analysis. The expected results include improved living conditions, enhanced job satisfaction, and greater productivity, contributing to sustainable urban development and better work-life balance.